A PRAGMATICS STUDY ON DEIXIS IN THE SPORT ARTICLES OF THE JAKARTA POST NEWSPAPER - Rosdiana, Ely (Jurnal Ilmiah Mahasiswa FIB, 2013)
Deixis is a linguistic knowledge that is less familiar to some people. The word is in the sentence or utterance where the meaning is not stable. Deixis is used in several linguistic terms, such as spoken language and written language. In written language, deixis is more difficult because we may not know the speaker and the hearer and the time is also unpredictable unless there is a clue showing the exact time. The writer intends to analyze deixis contained in sentences in the newspaper article. This study is conducted to find out, (1) deixis types contained in sentences in the article, (2) reference deixis in sentences in the article. The writer uses Grundy’s theory. This research is a qualitative study and classified as document analysis because the writer analyzes some sport articles of Jakarta Post newspaper. this study the writer finds 73 sentences containing deixis of the total sentences containing these deixis, person deixis in 40 sentences, place deixis in 10 sentences and time deixis in 23 sentences. In this study, the type of deixis most commonly found is person deixis.   Keywords: Deixis, Types of Deixis and Article.